2013
DOI: 10.1016/j.semnephrol.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulation in Renal Disease Models

Abstract: Activation of the complement system is tightly regulated by plasma and cell-associated complement regulatory proteins (CRPs), such as factor H (fH), decay-accelerating factor (DAF), and membrane cofactor protein (MCP). Animal models of disease have provided considerable insights into the important roles for CRPs in the kidney. Mice deficient in fH have excessive fluid phase C3 activation and inactivation leading to deposition of iC3b in glomerular capillary walls (GCW), comparable to dense deposit disease. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 94 publications
0
22
0
1
Order By: Relevance
“…Inherited and acquired abnormalities of membrane cofactor protein, a complement regulator present in the renal TI [2], [30] can underlie atypical hemolytic uremic syndrome and acute kidney injury, respectively [8]. Given their similar distributions and shared functions, our findings with Crry in the kidney are relevant to these human disease states in which there is abnormal complement regulation by membrane cofactor protein [31].…”
Section: Discussionmentioning
confidence: 73%
“…Inherited and acquired abnormalities of membrane cofactor protein, a complement regulator present in the renal TI [2], [30] can underlie atypical hemolytic uremic syndrome and acute kidney injury, respectively [8]. Given their similar distributions and shared functions, our findings with Crry in the kidney are relevant to these human disease states in which there is abnormal complement regulation by membrane cofactor protein [31].…”
Section: Discussionmentioning
confidence: 73%
“…Several animal studies have demonstrated a beneficial effect of blocking the alternative C pathway in LN (84). Although little work has been done with C inhibition in human LN, effective inhibitors are available, including a monoclonal antibody against C5 (eculizumab) and a small molecule C5a receptor blocker (CCX168) (85).…”
Section: Controlling Renal Inflammation In Lnmentioning
confidence: 99%
“…In contrast to widespread expression in humans, in mice and rats the CD46 molecule is exclusively expressed in testis. Mice and rats also have complement receptor 1-related gene protein y (Crry) that regulates C3 activation and has CD46 and CD55 like activity (Naik et al, 2013). …”
Section: Complement System and Normal Pregnancymentioning
confidence: 99%